Analysis of the marketing activities of the INEX-SDA non-profit organization - Zusková, Michaela; Cook, Gina, 1970-; Černá, Iveta, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
Non-profit organizations are an integral part of the Czech economy and important partner for the government. In today's economic environment, NGOs face increasing competition not only from other similar institutions, but also from for-profit oriented companies. They are, therefore, forced to adopt entrepreneurial marketing techniques in order to succeed in the market. The aim of this Master Thesis is to analyze the non-governmental, non-profit organization INEX-SDA including its marketing strategies, to interpret the results based on marketing theory and to suggest possible improvements that could lead to better public awareness of the chosen organization.
Vedoucí práce: Gina Cook
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses